2018
DOI: 10.14336/ad.2017.1129
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences among Elderly Patients with Primary Percutaneous Coronary Intervention

Abstract: Several epidemiological and clinical studies have shown that females with ST-segment elevation myocardial infarction (STEMI) have a higher mortality than males following primary percutaneous coronary intervention (PPCI). Many analyses of sex-based differences following STEMI have revealed conflicting results. Currently, more and more elderly patients with STEMI have undergone emergency interventional therapy. From January 2014 to December 2016, a total of 337 elderly patients with STEMI were enrolled in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…And women have a higher life expectancy than men, which is due to differences in deaths from injuries, lung cancer, and cardiovascular diseases, which may be related to the differential hormonal effects, genetic predisposition 21 and smoking habits 22 . In another eastern Asian study, elderly women with STEMI showed better clinical outcomes 1 year after primary PCI than men 23 . Furthermore, there was a higher smoking rate in men than women (52.3% vs. 5.1%) in that study.…”
Section: Discussionmentioning
confidence: 91%
“…And women have a higher life expectancy than men, which is due to differences in deaths from injuries, lung cancer, and cardiovascular diseases, which may be related to the differential hormonal effects, genetic predisposition 21 and smoking habits 22 . In another eastern Asian study, elderly women with STEMI showed better clinical outcomes 1 year after primary PCI than men 23 . Furthermore, there was a higher smoking rate in men than women (52.3% vs. 5.1%) in that study.…”
Section: Discussionmentioning
confidence: 91%
“…The “confirmed ACS” subgroup represented 1,195,524 patients, including 494,641 women. Patients included in the studies were admitted to emergency departments for chest pain, ACS suggestive symptoms according to the receiving physicians [ 10 , 12 , 16 , 17 , 18 , 20 , 21 ] or ACS suspicion from troponin measurement [ 11 , 13 ], or were hospitalized for ACS [ 9 , 14 , 15 , 19 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, all the studies were prospective and therefore did not rely on a posteriori collection of the symptoms of ACS presented by the patients. Data collection was standardized in each of the studies by systematic collection by the investigators [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Carrying out the analysis of the “Confirmed ACS” subgroup allowed us to analyze the symptoms even better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's roles as caregivers drive them to prioritize their families' needs over their own, or patriarchal social norms lead to difficulties in women being able to express their needs [3]. Sexbased disparities in outcomes may also simply be attributable to a sex-based predilection to the specific disease or underlying biological differences between men and women, as is seen in symptom and treatment patterns in women with acute coronary syndrome [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%